Effect of the pH pre-adjustment on the formation of In(2)W(3)O(12 )and In6WO12 powders: Cluster coordination and optical band gap - Paiva, Rafael Texeira de; Nogueira, Icamira Costa; Sczancoski, Julio Cesar; Lemos, Pablo Santana; Elias Matos, Jose Milton; Santos, Reginaldo Silva; Longo, Elson [UNESP]; Cavalcante, Laecio Santos (Elsevier B.V., 2020)
In this communication, diindium tristungstate (In2W3O12) and hexaindium tungstate (In6WO12) powders were synthesized by the co-precipitation method at different pH values and heat treatment at 1073 K for 2 h. X-ray diffraction patterns and Rietveld refinements were employed to analyze the long-range structural ordering as well as quantify the presence crystallographic phases, respectively. All powders obtained in pH ranging from 2 to 3.5 exhibited a mixture of In2W3O12 and gamma-tungsten oxide (gamma-WO3) phases. When prepared at pH close to 4, the powders presented both In2W3O12 and In6WO12 phases. All these crystalline structures were simulated in a three-dimensional visualization program by adopting the Rietveld refinements analysis as input data. The ultraviolet-visible spectra were employed to estimate the optical band gap energy of all powders for the first time. (C) 2019 Published by Elsevier Espana, S.L.U. on behalf of SECV.
Keywords: In2W3O12; In6WO12; Rietveld refinement; Clusters; Optical band gap